2010
DOI: 10.1186/1742-2094-7-16
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of tumor necrosis factor-α-induced interleukin-6 synthesis in glioma cells

Abstract: BackgroundInterleukin (IL)-6 plays a pivotal role in a variety of CNS functions such as the induction and modulation of reactive astrogliosis, pathological inflammatory responses and neuroprotection. Tumor necrosis factor (TNF)-α induces IL-6 release from rat C6 glioma cells through the inhibitory kappa B (IκB)-nuclear factor kappa B (NFκB) pathway, p38 mitogen-activated protein (MAP) kinase and stress-activated protein kinase (SAPK)/c-Jun N-terminal kinase (JNK). The present study investigated the mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 20 publications
5
107
0
5
Order By: Relevance
“…43 On the other hand, IL-6 is not a classical pro-inflammatory cytokine and exerts several anti-inflammatory actions such as downregulation of IFN-γ, IL-1β, and TNF-α. 44 However, to the best of our knowledge there are no reports on antinociceptive action of IL-6, despite the IL-6-mediated liberation of opioid peptides from leukocytes already mentioned above.…”
Section: Pronociceptive Cytokinesmentioning
confidence: 99%
“…43 On the other hand, IL-6 is not a classical pro-inflammatory cytokine and exerts several anti-inflammatory actions such as downregulation of IFN-γ, IL-1β, and TNF-α. 44 However, to the best of our knowledge there are no reports on antinociceptive action of IL-6, despite the IL-6-mediated liberation of opioid peptides from leukocytes already mentioned above.…”
Section: Pronociceptive Cytokinesmentioning
confidence: 99%
“…The phosphorylation levels of these two sites are dramatically increased upon stimulation of NF-kB activity. 29,30 Moreover, studies show that tumor cell apoptosis induced by anticancer reagents is associated with decreased p65 phosphorylation at Ser536 residue, [31][32][33] suggesting that p65 Ser536 phosphorylation is important for maintaining cancer cell survival and can be inhibited by anticancer reagents. In this study we showed that not only phosphorylation of Ser536 but also phosphorylation of Ser468 is downregulated during HDAC inhibitor-induced apoptosis of EC cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, when produced in higher amounts during neuropathology, they are known to potentiate glutamate induced cytotoxicity by inhibiting glutamate transport to the glial cells from the synaptic cleft [12,[16][17][18][19]. Even development of MHE has been described to be dependent more on enhanced inflammatory markers than the severity of CLF or HA in the CLF patients [20].…”
Section: Introductionmentioning
confidence: 99%